(untitled) (KYAMC Journal, 2017)
Lutembacher’s Syndrome is a rare heart disease first described by Lutembacher, is a combination of a congenital atrial septal defect (ASD) and acquired mitral stenosis (MS). Traditionally Lutembacher syndrome has been corrected by surgical treatment. If diagnosis could be done earlier, surgical closure of ASD with replacement of mitral valve bears a good prognostic value. Cases were reported where patients treated percutaneouly with a combined Inoue balloon valvuloplasty and septal defect closure using the Amplatzer septal occlusion device. Our patient Mrs. Kohinoor Begum, 26 years old, non diabetic, non hypertensive, admitted in khwaja Yunus Ali Medical College & Hospital (KYAMCH) on 03.04.2013 with the complaints of respiratory distress and chest pain for 3 years. There was history of recurrent attack of fever in childhood. Subsequently she developed MS from Rheumatic carditis. ASD was congenital in origin. After thorough perioperative evaluation pericardial patch closure of ASD with open mitral commissurotomy was done. Postoperative followup 6 months after operation showed no residual shunt with adequately functioning mitral valve. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 484-487